APPLICATION OF THE CARD SORT ACTIVE LEARNING METHOD TO IMPROVE STUDENT LEARNING ACTIVITY IN CLASS - Della Mora; Oce Datu Appulembang; Widiastuti Widiastuti (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
Learning activeness is an activity that focuses on student development physically, intellectually, emotionally, and mentally so that students are not only recipients of information but are involved in learning. Student activeness is very important because it affects student motivation, engagement, and learning outcomes. Low student activeness can be seen from students being sleepy, not paying attention to the teacher's explanation, not focusing, and not having the courage to ask questions and express opinions. The writing of this final project aims to describe student learning activity through the application of card-sort-type active learning methods in the fifth grade. The research method used is descriptive qualitative. The results showed that, after applying the card sort method, the average learning activeness of fifth-grade elementary school students increased from 53.33% to 80.67%. In conclusion, the card sort type of active learning method can enhance learning activities by providing opportunities for students to be actively involved in the learning process. The author's suggestion for future researchers is to continue investigating the application of active learning methods such as card sort, to enhance learning motivation.